PENGENALAN PEMASARAN MELALUI E-COMMERCE DAN MEDIA SOSIAL PADA UMKM DI DESA MEDAN KRIO - Mulyani, Sri; Astuti, Citra; Aulia, Muhammad Rizki; Amri, Syaiful (MAJU : Indonesian Journal of Community Empowerment, 2025)
This type of research is a qualitative research conducted by collecting data through informants who are MSMEs in Medan Krio Village. This research was conducted using interview techniques related to the introduction of e-commerce and social media to MSMEs in Medan Krio Village and documentation. The teaching carried out in using e-commerce and social media that was carried out went well and supported by MSMEs in Medan Krio Village. The participants asked many questions related to the use of e-commerce and social media. With this teaching, it is hoped that MSMEs can increase their insight and knowledge provided and can be more effective and efficient in increasing their income. It is hoped that with this teaching, MSMEs can increase income and the economy in Medan Krio Village, which is in accordance with our purpose of conducting this teaching so that the Community and MSMEs can follow technological developments in increasing sales.